THE EFFECT OF WILLIAM FLEXION EXERCISE (WFE) ON LOW BACK PAIN AMONG NURSING IN DR. M. YUNUS HOSPITAL, BENGKULU CITY - Septiyanti Septiyanti; Milda Putri Dinanty; Hermansyah Hermansyah (Proceeding B-ICON, 2022)
Lower Back Pain (LBP) is pain that is felt in the lower back area. Based on the 2020 International Association for the Study of Pain, it shows that the results of the prevalence of LBP are estimated at ± 7.5% of the global population or around 577 million people who experience LBP. In Indonesia, data on the number of LBP sufferers themselves is not known with certainty, but it is estimated that the numbers vary from 7.6% to 37% of the total population in Indonesia. The prevalence of musculoskeletal diseases in Indonesia is 7.9% and there are three provinces with the highest prevalence, namely Aceh (13.3%), Bengkulu (10.5%) and Bali (8.5%). The purpose of this study was to determine whether there was an effect of William Flexion Exercise (WFE) on lower back pain for nurses at RSUD Dr.M. Yunus Bengkulu City. This type of research is quasi-experimental with a pre-post test design with control group, the sample is inpatient nurses in Seruni and Melati rooms at RSUD Dr. M. Yunus City of Bengkulu, totaling 28 people using Purposive Sampling technique. The results showed that the average value of low back pain before being given intervention in the intervention group was 6.00 while the average value of low back pain before being given intervention in the control group was 5.00. There is a difference in the average value of low back pain in the intervention group 1.00 and the control group 2.00. It can be concluded that William's flexion exercise is more influential than McKenzie's extension exercise.